Report on the International Workshop on South Asian Women in International Security, Building Cooperative Networks, July 30-31, 1998 and the Regional Workshop on Women in International Security, Exploring South Asian Initiatives July 29-30, 1999 (NIAS report ;, 2002)
Proceedings of the two workshops held at Bangalore.